1998
DOI: 10.1088/0741-3335/40/6/005
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of density fluctuations in the Tore Supra tokamak

Abstract: It is believed that radial anomalous transport in tokamaks is caused by plasma turbulence. Using infra-red laser scattering techniques on the Tore Supra tokamak, statistical properties of the density fluctuations are studied as a function of the scales in ohmic as well as additional heating regimes using the lower hybrid or the ion cyclotron frequencies. The probability distributions are compared to a Gaussian in order to estimate the role of intermittency which is found to be negligible. The temporal behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Additionally, the three-dimensional geometry should further contribute to deviations from pure 2D fluid turbulence. Spectral indices of −3 and −4 have been found for the density fluctuation power spectra in TEXTOR [30] and Tore Supra [31]. Other theoretical treatments of fusion plasma turbulence predict a value of −4 [32,33].…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, the three-dimensional geometry should further contribute to deviations from pure 2D fluid turbulence. Spectral indices of −3 and −4 have been found for the density fluctuation power spectra in TEXTOR [30] and Tore Supra [31]. Other theoretical treatments of fusion plasma turbulence predict a value of −4 [32,33].…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, it is not surprising that when using a much smaller number of points, reported in an earlier paper, 9 we were unable to unveil clearly the presence of coherent structures. However, no significant time delay is recorded, suggesting that the mechanism behind this cross correlation is coherent structures coupling rather than an energy transfer in the k space.…”
Section: Discussionmentioning
confidence: 67%
“…6 the cross-correlation coefficients for ⌬kϭϮ3 and Ϯ4 cm Ϫ1 . 9 and replotted for the same data sets, hence using the same time resolution, in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations on the Tore Supra tokamak showed that the autocorrelation time of the three-dimensional energy, which could be linked to the eddy turnover time, decreases with decreasing scale. Because in the enstrophy subrange the eddy turnover time does not depend on the scales, it appears that the studied fluctuations, between 0.4 and 2 cm, lie in the energy cascade subrange [25].…”
Section: P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 94%